2010
DOI: 10.2105/ajph.2008.158840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Economic Assets on Sexual Risk-Taking Intentions Among Orphaned Adolescents in Uganda

Abstract: Objectives-To examine the effect of economic assets on sexual risk taking intentions among school-going AIDS-orphaned adolescents in rural Uganda.Methods-AIDS-Orphaned adolescents from fifteen comparable schools were randomly assigned to control (n=133) or treatment (n=127) conditions. Treatment participants received child savings accounts, workshops, and mentorship. This economic intervention was in addition to the traditional care and support services for school-going orphaned adolescents (counseling and sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 43 publications
9
107
0
1
Order By: Relevance
“…Data are derived from in-person interviews with adolescents and school administrative records. The in-person interviews were conducted annually by trained research assistants (21, 24, 29, 30). School attendance and examination performance data come from school records and unannounced roll-calls conducted by the program staff post-baseline assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are derived from in-person interviews with adolescents and school administrative records. The in-person interviews were conducted annually by trained research assistants (21, 24, 29, 30). School attendance and examination performance data come from school records and unannounced roll-calls conducted by the program staff post-baseline assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Results from these matched CSA programs demonstrate a reduction in levels of depression and hopelessness (18); improved HIV preventive attitudes and behaviors (19, 21); improved self-concept and educational achievement (22); and increased financial resources (23, 24). These findings are in line with prior research of transfers (CCT) which have shown positive effects on adolescents (25).…”
Section: Introductionmentioning
confidence: 99%
“…An experimental transfer scheme in Uganda demonstrated that the provision of transfers through saving accounts, workshops and mentorship led to a reduction in sexual risk-taking among participant children (Ssewamala, Han, Neilands, Ismayilova, & Sperber, 2010).…”
Section: Child Marriagementioning
confidence: 99%
“…Children in both groups received mentorship sessions throughout the intervention period. A detailed explanation of the intervention is provided elsewhere (see Ssewamala & Ismayilova, 2009;Ssewamala, Han, & Neilands, 2009;Ssewamala, Han, Neilands, Ismayilova and Sperber, 2010;.…”
Section: Study Design and Datamentioning
confidence: 99%